Analisis Iklim Mikro pada Budidaya Padi dengan Sistem Tanam Legowo Nyisip - I Wayan Adiguna; I Wayan Tika; Sumiyati Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2020)
This research was conducted to determine the effect of nyisip in raw of legowo planting system toward microclimate and paddy’s productivity of Cigeulis variety. This research using completely randomized design, with six treatments and 3 replications, they are: K0 (the treatment which appropriated to farmers custom), K1 (the treatment of legowo 2:1 nyisip), K2 (the treatment of legowo 3:1 nyisip), K3 (the treatment of legowo 4:1 nyisip), K4 (the treatment of legowo 5:1 nyisip) and K5 (the treatment of legowo 6:1 nyisip). The result of this research shown that the treatment of K1 got the higest intensity of sun shine at 23.817 lux and got the highest temperature at 27,20°C. The treatment of K0 has the highest relativity humudity at 79,30%. The treatment of K5 is the highest productivity per area at 6,06 ton/ha.